2021
DOI: 10.25259/ijdvl_31_20
|View full text |Cite
|
Sign up to set email alerts
|

Hindi translation and validation of quality of life score in Indian patients with epidermolysis bullosa; and its correlation with the clinical severity assessment scores: A cross-sectional study

Abstract: Background: Quality of life (QoL) has not been evaluated in Indian patients having epidermolysis bullosa (EB). Aims: The aims of the study were to measure health-related QoL in Indian patients having EB using the quality of life in epidermolysis bullosa (QoLEB) questionnaire, and to find its correlation with clinically measured disease severity. Methods: In this observational cross-sectional study, the QoLEB questionnaire was translated from English to Hindi (QoLEB-Hin) and culturally adapted without a cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The validity and reliability of the QOLEB instrument in quantifying functional and emotional aspects in patients with various EB types has already been shown for the original version, as well as for the Dutch, Spanish, Brazilian-Portuguese, Farsi, and Hindi translations [11,[13][14][15][16][17][18][19][20]30]. Moreover, QOLEB has been successfully employed in an online English cross-sectional survey on features and impact of EBS [31], and in a short-term prospective study on correlation between disease severity score, wound evolution, and QoL in DEB patients [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The validity and reliability of the QOLEB instrument in quantifying functional and emotional aspects in patients with various EB types has already been shown for the original version, as well as for the Dutch, Spanish, Brazilian-Portuguese, Farsi, and Hindi translations [11,[13][14][15][16][17][18][19][20]30]. Moreover, QOLEB has been successfully employed in an online English cross-sectional survey on features and impact of EBS [31], and in a short-term prospective study on correlation between disease severity score, wound evolution, and QoL in DEB patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…The developers of the questionnaire reported that EB patients from the age of 11 years were able to complete the QOLEB without parental assistance [11]. The QOLEB has been shown to discriminate between different EB types and severity scores evaluated using the "Epidermolysis Bullosa Disease Activity and Scarring Index" (EBDASI) and the "Birmingham Epidermolysis Bullosa severity score" (BEBs), and to correlate with DLQI, the Stanford Health Assessment Questionnaire for Mobility, and the Hospital Anxiety and Depression Scale [11,19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation